Teaching and Learning English Grammar for Communication by Using B-SLIM Teaching Technique for Year III Students of English Pedagogy, Faculty of Education, Souphanouvong University - PANFONGPHET, Sipaseuth (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
The objectives of the research are to study the efficiency of teaching plan according to criteria 80/80, to study the effective of students’ learning, and to study the students’ satisfaction for teaching B-SLIM. The simple group is 22 students in year three of English Teacher Programme in Souphanouvong University and experiment group was the third year students of English teacher Programme. The theoretical acquired by Cognitive Science Concept of Piaget, Vygotsky and Constructivism of Bruner in B-SLIM Teaching Model to create English Grammar Teaching plans which consist of five teaching plans of English Grammar subject in order to experimental teaching-learning within 10 hours. The equipment of research consists of the test form for learning achievement assessment is the four multiple choices in 20 questionnaires. There are the implementation and behavior evaluation form, sub-test form and 20 questionnaires for satisfaction evaluation. The Index of Item Objective (IOC) of teaching plan and questionnaires are between 0.8-1.00; the difficulty value (p) is between 0.32-0.77; the range value (r) is between 0.26-0.77 and reliability of questionaires are 88.50%. The result of research as followed: 1) The value of efficiency of teaching plan of English Grammar subject by using B-SLIM teaching technique for year two students of English teacher programme in Souphanouvong University is 90.18/89.09 that are higher than critiria 80/80. 2) The effective index of the effective of statistic subject learning by using B-SLIM teaching methodology for year three students of English teacher programme in Souphanouvong University is totally 0.863 or 86.30%. 3) The students satisfy teaching-learning on English Grammar subject by using B-SLIM teaching technique for year three students of English teacher programme in Souphanouvong University is totally in high level. Conclusion: English Grammar teaching-learning by using B-SLIM teaching technique which was created and develop had appropriate efficiency that can apply in teaching-learning in reqards to build qualitative students in which influence to students’ performance outcomes and achievement, and students satisfied in high level.